Narrativas entrelaçadas : práticas de letramentos digitais na formação de professores de língua portuguesa - (:unkn) unknown (Universidade Estadual de Goiás, 2025)
This dissertation, developed in the Postgraduate Program in Language, Literatu re, and Interculturality, investigates the construction of the concept of literacy in the training of Portuguese Language teachers. The primary aim is to examine how literacy concepts are constructed during workshops with Portuguese language teachers who w ork with 5th year students in the Early Years. The theoretical foundation draws on the works of Barton, Hamilton, Ivanic (2000), Kalantzis, Cope and Pinheiro (2020), Kleiman (1995), Monte Mór (2019, 2020), Rojo (2012), and Soares (2020), supporting a discu ssion about digital literacy and cultures. The adopted methodology combines qualitative and quantitative research with an interpretative approach, anchored in the studies of Lüdke and André (2014) and Minayo (2009, 2014). This approach aims to understand e xperiences and quantify the data. For data generation, we invited Portuguese language teachers working in the 5th year of the Early Years in 2025, at the Municipal Department of Education and Culture of Jussara, Goiás. We used the following instruments: a) Mini story productions by teachers with the theme "everyday scenes"; b) Recorded and transcribed interactions between participants during workshop discussions; c) Questionnaires (Google Forms) carried out during the data generation process, also transcrib ed; d) Analysis of the social practices in the mini stories; e) Digital literacy workshops to understand literacy concepts, social practices, and the mini story genre. The choice of everyday scenes as a starting point for literacy practices is based on und erstanding linguistic needs in various contexts, aiming to explore new discursive genre languages. The final feedback from participants demonstrates that the workshops successfully integrated literacy practices into teaching and learning from a literacy pe rspective.
Interwoven narratives : digital literacy practices in the training of portuguese language teachers
Keywords: Formação docente; Letramento digital; Prática social; Miniconto; Teacher training; Digital literacy; Social practice; Mini story; Genre languages; LINGUISTICA, LETRAS E ARTES::LETRAS; LETRAS::TEORIA LITERARIA; CIENCIAS HUMANAS::EDUCACAO